Deposition, characterization, and thin-film-based chemical sensing of ultra-long chemically synthesized graphene nanoribbons - Abbas, Ahmad N.; Liu, Gang; Narita, Akimitsu; Orosco, Manuel; Feng, Xinliang; Muellen, Klaus; Zhou, Chongwu (Journal of the American Chemical Society, 2014)
Bottom-up synthesis of graphene nanoribbons (GNRs) is an essential step toward utilizing them in electronic and sensing applications due to their defined edge structure and high uniformity. Recently, structurally perfect GNRs with variable lengths and edge structures were created using various chemical synthesis techniques. Nonetheless, issues like GNR deposition, characterization, electronic properties, and applications are not fully explored. Here we report optimized conditions for deposition, characterization, and device fabrication of individual and thin films of ultra-long chemically synthesized GNRs. Moreover, we have demonstrated exceptional NO2 gas sensitivity of the GNR film devices down to parts per billion (ppb) levels. The results lay the foundation for using chemically synthesized GNRs for future electronic and sensing applications. © 2014 American Chemical Society.
CRIS-Team Scopus Importer:2023-03-20